Field Measurements for Forest Carbon Monitoring A Landscape-Scale Approach - Hoover, Coeli M. (Springer Netherlands : Imprint: Springer, 2008)
This volume is a comprehensive guide to the methods and techniques employed in forest carbon inventory and monitoring. Since forest carbon research is interdisciplinary, it is unlikely that any one investigator will possess expertise in all of the types of measurements needed to conduct forest carbon research at scales larger than a forest stand. Techniques used to characterize standing stocks of carbon in a forest, measure key carbon fluxes, and collect related data (such as forest canopy nitrogen concentrations and meteorological measurements) that are required to drive process models, develop predictive relationships, and link to remote sensing data are described in detail. In addition to the measurement methods, the chapters include background information, necessary calculations, and equipment requirements. The field of forest carbon research is growing rapidly, and Field Measurements for Forest Carbon Monitoring provides an excellent reference for the many and varied techniques necessary to characterize the forest carbon cycle. While the book outlines an entire forest carbon monitoring program, each chapter stands alone as a reference for measuring the variable described, and sufficient background discussion is included to allow investigators to determine if a particular measurement is warranted in their research program.